(untitled) (LACCEI, 2024)
This paper shows the results of the estimation of the Gini index from workers in the Chilean construction industry. As known, this coefficient is a measure of statistical dispersion intended to represent the income inequality within a social group. The Organization for Economic Cooperation and Development (OECD), the World Bank, and the United Nations Development Program (UNDP) have calculated this index for a significant number of countries in order to classify them according to their level of inequality, where this study may help expand the reach of this type of analyses to other economic sectors. Thus, in this research the Gini index for workers of the Chilean construction industry was calculated for each geographical region in Chile, with the purpose of knowing the different economic conditions among the construction workers in the different regions of Chile, in terms of the workers’ salary inequality, and along with it, to complement the limited studies in this regard. To estimate the Gini index, it was necessary to collect the data available in Chilean institutions. The results showed that there are no significant differences in terms of inequality when the Gini index is calculated for homogeneous groups of construction workers however, when the analysis considers workers with different academic backgrounds (with and without professional degrees) important inequality levels appear.